2010
DOI: 10.1177/0145445510362576
|View full text |Cite
|
Sign up to set email alerts
|

Vasovagal Syncope and Blood Donor Return: Examination of the Role of Experience and Affective Expectancies

Abstract: Vasovagal sensations (e.g., dizziness, nausea, and fainting) are one of the main reasons people find blood donation unpleasant. A better understanding of predictors of vasovagal sensations during blood donation could inform interventions designed to increase donor return rates. The present investigation examined the extent to which experience with blood donation and vasovagal sensations during blood donation uniquely predict the likelihood of donor return, even when controlling for affective expectancies. Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
2
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 18 publications
4
28
2
8
Order By: Relevance
“…This is consistent with previous research demonstrating that increased donation experience contributes to less adverse reactions during blood donation (France et al, 2005;Meade et al, 1996). Moreover, recent research has shown that experienced donors displaying fewer adverse reactions are more likely to donate in the future (Olatunji, Etzel, & Ciesielski, 2010). Related research has also shown that a decrease in fainting symptoms during prior donations is proportional to an increase in the likelihood of donating blood in the future (France et al, 2004).…”
Section: Injection-fearful Participantssupporting
confidence: 90%
“…This is consistent with previous research demonstrating that increased donation experience contributes to less adverse reactions during blood donation (France et al, 2005;Meade et al, 1996). Moreover, recent research has shown that experienced donors displaying fewer adverse reactions are more likely to donate in the future (Olatunji, Etzel, & Ciesielski, 2010). Related research has also shown that a decrease in fainting symptoms during prior donations is proportional to an increase in the likelihood of donating blood in the future (France et al, 2004).…”
Section: Injection-fearful Participantssupporting
confidence: 90%
“…Anksiyete ile vazovagal reaksiyonların ilişkili olduğu sonucuna varılmıştır. 3 Enjeksiyon korkusu olan (n=108) ve enjeksiyon korkusu olmayan (n=338) kan vericileri ile yapılan bir ça-lışmada (n=446), enjeksiyondan korkan katılımcı-ların, anlamlı derecede daha genç oldukları, daha az kan bağışı deneyimine sahip oldukları, daha yüksek kan bağışı öncesi anksiyete ve iğrenme (tiksinme) bildirdikleri, kan bağışı sırasında daha sık baygınlık semptomları gösterdikleri ve kan bağışı deneyiminden daha hoşnutsuz oldukları saptanmıştır. 35 Kan bağışına bağlı anksiyeteyi azaltmaya yönelik girişimsel çalışmalar, kaygı ve endişe hali-nin kan bağışı işlemi sırasında olumsuz tepkilerin daha yüksek oranlarda görülmesiyle ilişkili olduğunu doğrulamıştır.…”
Section: Kan Bağişina Bağli Kompli̇kasyonlarin Geli̇şmesi̇ni̇ Etki̇leyen Eunclassified
“…35 Kan bağışına bağlı anksiyeteyi azaltmaya yönelik girişimsel çalışmalar, kaygı ve endişe hali-nin kan bağışı işlemi sırasında olumsuz tepkilerin daha yüksek oranlarda görülmesiyle ilişkili olduğunu doğrulamıştır. 3,29,38 İ İl lk k k ke ez z k ka an n b ba ağ ğı ış şı ın nd da a b bu ul lu un nm ma a: : İlk kez kan bağışında bulunanlarda vazovagal reaksiyonların deneyimli kan vericilerine göre daha yüksek oranda görüldüğü tespit edilmiştir. 6,11,16,18,31,32,39 Bu da ilk kez kan bağışında bulunanların kaygı düzeylerinin düzenli olarak kan bağışında bulunanlara göre daha yüksek olmasından kaynaklanmaktadır.…”
Section: Kan Bağişina Bağli Kompli̇kasyonlarin Geli̇şmesi̇ni̇ Etki̇leyen Eunclassified
See 2 more Smart Citations